Pasantía en la Empresa: Ingeniería y Consultoría de Colombia SAS (ICC), ejecutando actividades como Ingeniero Auxiliar en obras civiles (2022)
Ingeniería y Consultoría de Colombia SAS (ICC), is a company dedicated to the design, execution and construction o f civil works. It has a great knowledge of the construction and civil works market, allowing the integration of the knowledge and experience of different actors to create and develop innovative projects that have a positive impact on cities and people. Cur rently, we are executing vertical and horizontal signage, demarcation with cold plas tic paint, supply and application of primer, supply and installation of traffic signs, studs, studs and speed reducers and repair of existing signs, all this in the city of Boyacá, giving priority to the most critical points and always seeking to u needs and expectations of citizens. Duitama nderstand the This document represents the work done as an intern during the resident engineer internship to support future assignments installation of signs, studs, studs such as: supervision, elaboration, painting and and speed reducers.